The Dialectics of Self and Space in Zackie Achmat’s “My Childhood as an Adult Molester: : A Salt River Moffie” (1995) and Thomas Mann’s Death in Venice (1912) - Sinha, Aman (Journal of Literary Studies, 2025)
In his 1995 short memoir titled “My Childhood as an Adult Molester” (1995), writer and activist Zackie Achmat reflects on his sexual experiences as a child and adolescent, engaging in sex with white adult men in a racially segregated Cape Town, during the 1970s and 80s. Through recurrent spatio-temporal shifts in the narrative, Achmat’s autobiographical subject renders a violently segregated space and its cartography as permeable and fluid as the bodies that inhabit it. In this framework, a dialectic between space and subject construction emerges in which space writes the self, as much as the self writes the space. Desire is mapped onto momentary stasis rooted within the everyday, instead of a sovereign sexual subject navigating urban space. This conception operates in stark contrast to spatial engagements historically narrativised in Euro-American queer contexts. For instance, in Thomas Mann’s Death in Venice (1912), Aschenbach’s pursuit of Tadzio in a disease-stricken Venice manifests at the narrative level as premonitions of his eventual demise. Even though Daniel Marshal argues that his pursuit is suggestive of a queer agent consciously redoing space-time, his relationship with the decaying urban space remains merely that—symbolic of his departure from normative engagements with space. Alternatively, Achmat’s rendition offers a critique of racial and sexual normativity at multiple levels. It goes beyond a politics of identity-driven sexual morality and offers a model of sexual subjectivity in which fighting both the racialisation and heterosexualisation of space operates as practices that are wound up with each other. In that sense, it provides a framework for locating possibilities of critique in queer literary production that aims at intertwining conceptions of queer freedom with protests against racial unevenness in 21st-century South Africa.